MAJOR GOAT MILK PROTEIN: SEPARATION AND CHARACTERIZATION BY “LAB-ON-A-CHIP” MICROFLUIDIC ELECTROPHORES - DOS SANTOS, ALESSA SIQUEIRA DE O.; MEURER, VANEIDA MARIA; COSTA, FABIANO FREIRE; DE PAIVA, IGOR MOURA; FOGAÇA, GISELE NOGUEIRA; DO EGITO, ANTÔNIO SILVIO; FURTADO, MARCO ANTONIO MOREIRA; MARTINS, MARTA FONSECA (Boletim do Centro de Pesquisa de Processamento de Alimentos, 2018)
This work presents the electrophoretic profile of goat and cow milk samples and their mixtures using microfluidic and conventional electrophoresis. The microfluidic method allowed the separation of the major caseins from milk, excepting the goat κ-casein. Besides, the major whey proteins were separated with perfect distinction of A and B β-lactoglobulin variants. Comparing to SDS-PAGE, a variation in the molecular weight was observed in all milk proteins. However, A and B β-lactoglobulin variants could not be isolated using SDS-PAGE. Although urea-PAGE did not show high resolution among whey proteins, γ-, κ-, β-, and α-caseins were clearly identified. This method also showed a lower limit detection of cow milk in mixture samples than the "lab-on-a-chip" electrophoresis. In both methods, the highest linearity obtained from plotting total percentage against cow milk concentration was observed by using cow αs1-casein (R2 = 0.986 and R² = 0.973). This result indicates that microfluidic electrophoresis is an effective tool to detect the presence of some proteins in goat and cow milk, and in mixtures. Microfluidic chip technology might will complement the current methods for analyzing milk proteins, highlighting its speed amount of reagents and whey protein separation, which showed a better result than urea or SDS-PAGE